Effect of Transglutaminase Cross-Linked Rapeseed Protein on Cake Quality - XIONG Wenfei, ZHU Shuxin, LU Shanshan, YAO Yijun, WANG Lifeng (Shipin Kexue)
The present study aimed to investigate the feasibility of replacing egg white protein by rapeseed protein cross-linked by transglutaminase (TG) at different percentages (0%, 25%, 50% and 75%) in the making of baked foods. Herein, the effectiveness of the application of TG-crosslinked rapeseed protein in sponge cake was comprehensively evaluated by analyzing the apparent morphology, microstructure, color, texture, water status, starch crystallinity and flavor. The results showed that with increasing level of TG-crosslinked rapeseed protein, the cake color gradually deepened, with the internal pores becoming finer and more uniform. The water distribution, state and texture analyses showed that as the substitution level of egg white protein increased, the water mobility and water-holding capacity were enhanced. At a substitution level of 75%, the hardness, cohesiveness, and chewiness increased by 3.4, 3.2, and 2.4 times, respectively, while the elasticity reduced by 24%. The cake with 25% substitution level exhibited a significant anti-aging effect, as evidenced by a 31.1% decrease in crystallinity. Meanwhile, the elasticity, cohesiveness, resilience and water status of this cake were comparable to those of the cake with 100% egg white protein. In addition, the results of electronic nose and electronic tongue assays indicated that the substitution of rapeseed protein did not adversely affect the cake flavor. These findings provide valuable scientific guidance for the application of TG cross-linked rapeseed protein as an alternative to egg white protein in the making of baked foods.